KEDISPLINAN GURU DALAM MEMBENTUK KARAKTER SISWA DALAM BELAJAR DI SMP ISLAM DARUSSA’ADAH MALANG - Muhammad Hanif Azhar; Ika Ratih Sulistiani; Zuhkhriyan Zakaria (VICRATINA, 2020)
Character is the initial foundation to instill in students to become a generation of noble character. Based on preliminary observations, the principal as a disciplined leader in something is expected to be able to understand and answer the problem: Teacher Discipline in Forming Student Characters in Learning in Darussa'adah Islamic Middle School Malang. The background of the above research the researchers formulated the problem, namely the solution to the delay of educators, student character, teacher discipline in forming student character in Darussa'adah Islamic Middle School Malang. The purpose of this study is to describe the solution to the delay of educators, student character, teacher discipline in forming student characters in Darussa'adah Islamic Middle School Malang. The conclusion from the research ijni is an educator must become uswah hasanah for students, starting from oneself to make themselves disciplined. The character values contained in learning at Darussa'adah Islamic Middle School Malang include several characters, namely: religiousness, cleanliness, honesty, independence, discipline, caring, love for the Indonesian homeland. Factors for the formation of student characters are family (parents), education (school), and environmental factors, second: penalties for students who violate.